Management of lung nodules newly found by virtual-assisted lung mapping: a case report - Masahiro Yanagiya; Masaaki Sato; Hideki Kuwano; Kazuhiro Nagayama; Jun Nakajima (Surgical Case Reports)
Abstract Background Virtual-assisted lung mapping is a novel bronchoscopic lung marking technique that uses virtual images to perform multiple concurrent dye marking of barely palpable pulmonary tumors. Subsequent chest computed tomography is required to confirm the locations marked. We here report a patient in whom computed tomography after virtual-assisted lung mapping unexpectedly revealed additional tiny pulmonary nodules. Case presentation A 64-year-old woman with a history of renal cell carcinoma presented with two pulmonary nodules suspicious of metastases from renal cell carcinoma. Because we anticipated that the nodules would be difficult to palpate intraoperatively, we performed virtual-assisted lung mapping prior to attempting to resect them. Computed tomography after mapping unexpectedly detected two additional nodules. Although the existing markings did not relate to the newly found nodules, we used imaginary auxiliary lines and anatomical landmarks to extend the lung map to incorporate the unexpected nodules. The additional nodules were successfully resected by thoracoscopic wedge resection. Pathologic examination identified all nodules as metastases from renal cell carcinoma, and the surgical margins were negative. Conclusions Imaginary auxiliary lines and anatomical landmarks extended the existing lung map of virtual-assisted lung mapping, enabling resection of unexpected pulmonary nodules found in post-mapping computed tomography images.